Abe Lincoln in Illinois. - Massey, Raymond; Rice, Elmer, 1892-1967.; Huston, Walter, 1884-1950.; Sherwood, Robert E. (Robert Emmet), 1896-1955.; Weill, Kurt, 1900-1950.; National Theatre Corporation (Washington, D.C.); Playwrights' Company; Richard L. Coe Theater Programs Collection (Library of Congress) (1938)
National Theatre, The Playwrights' Company, Maxwell Anderson, S.N. Behrman, Sidney Howard, Elmer Rice, Robert E. Sherwood, present Raymond Massey in Robert E. Sherwood's new play, "Abe Lincoln in Illinois," staged by Elmer Rice, settings by Jo Mielziner.
National Theatre, beginning October 3, 1938.
Cast: Frank Andrews, Raymond, Massey, Adele Longmire, Iris Whitney, George Christie, Arthur Griffin, Lewis Martin, Calvin Thomas, Harry Levian, Howard DaSilva, Everett Charlton, David Clarke, Kevin McCarthy, Herbert Rudley, Lillian Foster, Wendell K. Phillips, May Collins, Muriel Kirkland, Dorothy Allan, Marion Rooney, Hubert Brown, Albert Phillips, John Payne, Frank Tweddell, John Gerard, Thomas F. Tracey, Stuart McClure, John Triggs.
Title devised by Library staff.
"Program published by Clifton Aires, 1319 F. Street N.W. District 7433"--p. 9.
LC copy accompanied by playbill advertisement for Walter Huston in "Knickerbocker Holiday".
In: The Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Lincoln, Abraham, -- 1809-1865 -- Drama; Theater programs -- Washington (D.C.).; Theater programs -- 1938.; Playbills -- Washington (D.C.).; Playbills -- 1938.